2018
DOI: 10.1103/physrevx.8.041026
|View full text |Cite
|
Sign up to set email alerts
|

Topological Crystalline Materials of J=3/2 Electrons: Antiperovskites, Dirac Points, and High Winding Topological Superconductivity

Abstract: We present a theory of the high-spin generalization of topological insulators and their doped superconducting states. The higher-spin topological insulators involve a pair of J = 3/2 bands with opposite parity, and are characterized by their band inversion. The low-energy effective theory reveals that the topological insulators host four different phases characterized by mirror Chern numbers, at which boundaries two different patterns of bulk Dirac points appear. For the carrierdoped case, it is shown that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 76 publications
(131 reference statements)
3
46
0
Order By: Relevance
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recent predictions of bulk Dirac cones [3,4] and topological nature [5] in the vicinity of the Fermi energy, antiperovskite oxides are attracting a lot of attention [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. After the initial theoretical predictions, the chemical and physical characters of antiperovskite oxides have been extensively investigated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, recent developments have shown that emergent MFs appear as gapless Andreev bound states in topological superconductors (TSCs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14], which provide a potential candidate for fault-tolerant qubits for topological quantum computation [15]. The increased interest in topological materials has led to a proposal of versatile three-dimensional (3D) time-reversalinvariant (TR-invariant) TSCs, such as superconducting doped topological insulators (TIs) [16][17][18][19][20][21][22][23] and Dirac semimetals [24][25][26][27][28][29], which commonly host helical MFs forming Kramers pairs on their surfaces. Emergent MFs share some properties with elementary Majorana particles [30,31].…”
mentioning
confidence: 99%